Development Of Digital Comic Learning Media Using Canva In Science And Technology - Insiyah, Endah; Fatirul, Achmad Noor; Fiantika, Feny Rita (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This research aims to develop Digital Comic Learning Media Using Canva in the Science and Technology. The purpose of this development is to produce a product in the form of digital comic learning media using Canva with a Four-D learning design, so that students' motivation to learn will increase and understand the material being studied. The Four-D model, which is one of the development models of the Research Design Development method. The Four-D Model was developed by Thiagarajan et.al in shinta et.al (2023). This model consists of four main stages: 1) Define; 2) Design; 3) Develop; 4) Disseminate. Based on the results of the research conducted, the development of digital comic learning media using Canva has proven to be effective and feasible to use in the learning process. This media is able to present material in an interesting and interactive manner, which can increase students' interest and understanding. The process of creating digital comics with Canva also makes it easier for teachers and students to access, create learning content that suits the characteristics of students. Overall, Canva-based digital comics can be used as an innovative and effective alternative learning medium, which supports a more fun and student-centered approach to learning.